Hak Khiyar Dalam Perlindungan Konsumen Menurut Mazhab Syafi’i Dan Hukum Positif (Studi Kasus Jual Beli Buku Bersegel di Toko Buku Pustaka 2000 Kecamatan Lubuk Pakam) - Nasution, Leni Masnidar (STAI Serdang Lubuk Pakam, 2019)
Among muamalah activities is buying and selling. Today the practice of buying and selling is growing apart from all kinds of things one of them is a book. Nowadays, the sale of books is packaged with plastic seals so that it attracts buyers. One of these books was sold at the Bookstore Pustaka 2000 in Lubuk Pakam District. The practice of buying and selling is bizarre for some consumers / buyers. When further investigated, the vulnerability of neglected consumer rights makes the pattern of buying and selling in the shop contradict with Islamic law and Positive Law. This research is a field research with a qualitative approach using analytic descriptive method, the implication of which is by describing the author's analyzes of phenomena that occur in the midst of society within the object of research based on Islamic normative theory, especially according to the perspective Syafi'i school and Positive Law. According to the view of the Shafi'ite school in several Majmu books' Syarah al- Muhazzab and the book Nihayatu az-Zain Fi Irsyadi al-Mubtadi'in that every consumer and seller in trading activities has the same position before Islamic law. The practice of buying and selling books in the store according to the author's observations practically ignores consumer rights. Lack of socialization of knowledge and understanding of consumer protection, especially the right of khiyar according to Islamic law and positive law is the main factor why the practice of buying and selling books that are still wrong. This research concludes according to the author that buying and selling in the store is contrary to the concept of khiyar and positive law. In addition, the standard clause by the store according to the analysis of the writer does not apply the concept of khiyar and neglects the rights of consumers so that it is null and void.